(untitled) - Shakespeare, William (Cambridge, 1990)
An early play in five acts by William Shakespeare, performed 1594-95 and published in the First Folio of 1623. The story of the play was taken from a translation of a long Spanish prose romance entitled Diana by Jorge de Montemayor. Shakespeare added new characters--including Valentine, one of the "Two Gentlemen," whose "ideal" friendship with Proteus is so developed that the plot seems to glorify friendship over romantic love. The abrupt last scene suggests that something has gone wrong with the text, and certainly Shakespeare was never again to use such preposterous motivation for the behavior of his lovers. But it is also clear that Shakespeare was developing a new kind of high comedy that was later to find expression in The Merchant of Venice and Twelfth Night.
Keywords: Sự đài ải,Exiles; Kịch,Drama